If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -3 = -1 + -2y Reorder the terms: -3 + 2y = -1 + -2y Solving -3 + 2y = -1 + -2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2y' to each side of the equation. -3 + 2y + 2y = -1 + -2y + 2y Combine like terms: 2y + 2y = 4y -3 + 4y = -1 + -2y + 2y Combine like terms: -2y + 2y = 0 -3 + 4y = -1 + 0 -3 + 4y = -1 Add '3' to each side of the equation. -3 + 3 + 4y = -1 + 3 Combine like terms: -3 + 3 = 0 0 + 4y = -1 + 3 4y = -1 + 3 Combine like terms: -1 + 3 = 2 4y = 2 Divide each side by '4'. y = 0.5 Simplifying y = 0.5
| -5x(3x^2-2x+5)= | | 8b+2=5b+6 | | 3(2x+2)-2(x-1)= | | 8+7x=18+9x | | 5(7x+9)+2(9-x)= | | -8x+15=6x-2 | | 3-5x=7-3x | | -6(5n+7)=27-7n | | a-4a=2a+1-5d | | 5a+8=2a+8 | | 4y-7=y-7 | | -3t-8-7t=34+9t-2 | | -1(3x-5)=0 | | 25m+125=30m+50 | | (5x+x+3)+(4x+7)= | | m+.5=3m+.9 | | 7z-z=-3+2z-3-6 | | 15.3-2.4(6-a)=3a | | .2b+8=05b+14 | | -3(4x-5)+4x=6x-2 | | 4x=-2+2t | | -4(x+2)5x=13 | | 4x^2=x+5 | | -10x+y=22 | | (2y-1)(3y+2)(1-y)= | | 3x+10-8x=17x+12x-3 | | n-5=7-3n | | 25t+3t=252 | | p=3b+4v | | 9d-27+9= | | log(x+11)-log(x-4)=2 | | 5x^3-15x^2+5x-15=0 |